ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI PADA REVENUE CYCLE UNTUK MENINGKATKAN KUALITAS INFORMASI TOKO SUMBER REJEKI DI MALANG - Stanley Moeritty; Adhicipta Raharja Wirawan (CALYPTRA, 2018)
Sumber Rejeki Shop is one of the MSMEs of the grocery-type trading sector that sells daily necessities and becomes the object of this research. Like most MSMEs, Sumber Rejeki Shop still uses a manual system in the transactions of business entities and the absence of reports on the operations of business entities. Without a report, the business entity will have difficulty in making decisions. This study aims to design a computerized accounting information system of revenue cycle sections at Sumber Rejeki Stores to improve information qualitythrough the features contained in Sleekr software. This research uses observation and interview method to obtain data related to Sumber Sumber Rejeki. The result of this research is Sleekr software can produce detailed invoice document and can generate report related to business transaction, both sales report and accounting, which can assist decision making process of Sumber RejekiShop.